Factors that Associated with Stunting Cases in Children Under Two at The Working Area of Wonokusumo Health Center - Nuraini Wulandiana; Cintia Maulina (Media Gizi Kesmas, 2021)
Background: Stunting is one of the nutritional problems experienced by toddlers, nowadays. Based on data from Global Nutrition Reports in 2014, three million children under five in the world are malnourished every year, and globally, the bad impact of diseases caused by malnutrition reaches billions of dollars. This situation can be prevented by improving nutrition in the first thousand days of life which begins during mothers' pregnancy until the children age two years. Currently, According to data from riskesdas, Stunting in Surabaya increases rapidly. In 2013, the number of children diagnosed with stunting was 21 % and got its peak by 29% in 2018. Purpose: The study aims to identify the risk factors of stunting in children, especially in their two-year age or under, in a working area of Wonokusumo Health Center. Method: This research is an analytic observational study with a cross-sectional design. The sampling technique that is used is a non-probability sampling technique with a consecutive sampling method, totaling 56 children. Primary data were obtained by measuring the height of the children using microtoise, and interviewing the mothers using a questionnaire. Data analysis was performed using the chi-square test through the Epi Info 7.0 application. Result: The obtained-result of the research was a significant relationship between the inactivity of attending an integrated service post (posyandu: Pos Pelayanan Terpadu) with the stunting (P = 0.03; PR = 0.21). There was also no significant relationship between the number of children, the level of maternal knowledge, the state of mother's employment, the states of exclusive breastfeeding, the complete state of basic immunizations, and the history of infectious diseases (P> 0.05) with stunting. Conclusion: the absence of attending an integrated service post (posyandu: Pos Pelayanan Terpadu) is a factor that has a significant relationship with stunting among children under two in the working area of The Wonokusumo Health Center.